Fabrication of morphology-preserved microporous carbon from a zeolitic-like porous coordination polymer. Issue 2 (23rd January 2017) - Zhou, Bihang; Hua, Yinying; Cheng, Fujun; Duan, Jingui; Chen, Lingyun; Jin, Wanqin
Abstract : A new zeolitic-like microporous coordination polymer (PCP), [Zn2 (L)·2H2 O]· x guest, was firstly converted to morphology-preserved carbon rods with exclusive micropores and a large surface area for selective gas capture. Abstract : A new zeolitic-like microporous coordination polymer (PCP), [Zn2 (L)·2H2 O]·guest (namedNTU-17 ), with crb (BCT) topology was designed and prepared. Interestingly and unusually, it is the first time that such rod-shapedNTU-17 crystals could be converted to morphology-preserved carbon rods with exclusive micropores and a large surface area by using a facile method of direct thermal transformation. Gas adsorption and selectivity showed that these PCP dependent carbon rods are suitable solid adsorbents for CH4 purification.